Advanced Care Planning for Persons With Dementia in Primary Care: Attitudes and Barriers Among Health-Care Professionals. Issue 4 (October 2019) - Lee, Linda; Hillier, Loretta M.; Locklin, Jason; Lee, Jennifer; Slonim, Karen
Background: Advance care planning (ACP) provides clarity on goals and preferences for future health-care decisions, the timeliness of which is critical for persons with dementia. Aim: This study assessed Primary Care Collaborative Memory Clinic (PCCMC) health-care practitioners' desire for more education on ACP, capacity for and attitudes toward ACP, and current ACP practices in their regular family practice and in their PCCMC. Methods: Primary Care Collaborative Memory Clinic health-care professionals completed a questionnaire in which they rated their interest in learning various ACP-related topics (5-point scale: not at all to very much so), attitudes toward ACP, and the importance of and perceived degree of responsibility for ACP (5-point scale: not at all to extremely). Respondents estimated ACP completion in regular family practice and PCCMC. Results: Two hundred and sixty one surveys were completed. Mean knowledge ratings were moderate (M = 3.0) and mean ratings of interest in ACP topics were all high (median ≥ 4). Despite the perception that ACP is very important (M = 4.9) and the responsibility of PCCMCs (M = 3.7), the majority of respondents estimated that 40% or fewer patients have had ACP. Ratings of willingness to conduct ACP (M = 3.7) and comfort level (M = 3.4) were moderate but significantly exceeded ratings of ability (M = 2.9), comfort (M = 3.5), and confidence (M = 2.8). Conclusion: There was a striking disconnect between perceptions of the importance of completing ACP for persons with dementia and actual ACP completion rates. Primary Care Collaborative Memory Clinics may be in an ideal position to support ACP discussions; however, there is a need to improve health-care professionals' knowledge and attitudes toward ACP.